(untitled) (Oil and Gas Engineering, 2017)
The article features development of hydrocarbon fields analysis and problems of providing the reliability and durability of oilfield equipment and pipes system. The process of pipeline corrosion and causes that in-crease their intensification are considered. Pipe enameling process is also reviewed. Provided the estimation of glass-enamelaroilfield pipeline coating equipment as an effective way to avoid corrosion. The definition of “enamel” is given and the analysis of coating metal using enamel are made. The main factors and the agents for getting high-quality coverage are identified. Steel marks which are better exposed with enamel covering in terms of chemical composition are characterized and the range of pipes, connecting parts and its main advantages were determined. Keywords: hydrocarbons, metal corrosion, enamel coating glass-enamelar pipes.